Enlightening Ph.D. Students with the Elegance of Logic – My personal memory about Prof. Jose Meseguer - Chen, Shuo (Proceedings of the Festschrift Symposium in Honor of Jose Meseguer (LNCS 9200), 2015)
This article provides my recollection about how Prof. José Meseguer enlightened me to study security problems from the logic perspective. His lectures and advices are having a long term influence on my research career.